Frequency response of nonlinear networks using curve tracing algorithm - Ushida, A.; Yamagami, Y.; Nishio, Y. (2002 IEEE International Symposium on Circuits and Systems, 2003)
For designing of nonlinear circuits, it is very important to know the frequency response characteristics and the intermodulation. In this paper, we propose an efficient method for calculating the characteristic curves of nonlinear circuits, which is based on the harmonic balance method and a curve tracing algorithm for solving the determining equation. Firstly, applying the harmonic balance method to each element in the circuit, we obtain the determining equation which is realized by two coupled resistive circuits corresponding to the sine and cosine components. Then, the frequency response characteristic curve is calculated by solving the circuit with a STC (solution curve tracing circuit) of Spice.